Identification of point mutations in the envelope gene of Moloney murine leukemia virus TB temperature-sensitive paralytogenic mutant ts1: molecular determinants for neurovirulence. - Szurek, P F (1988)
ts1, a temperature-sensitive mutant of Moloney murine leukemia virus TB, induces hind-limb paralysis in mice. The DNA of both the ts1 and Moloney murine leukemia virus TB env genes has been sequenced, and the encoded amino acid sequences have been deduced from the DNA sequences. Four amino acids in the ts1 envelope protein have been identified which may be responsible for the ts1 phenotype, which includes temperature sensitivity, nonprocessing of Pr80env, and neurovirulence.